Reimagining Blended Learning Post-COVID-19: Insights from EFL Students’ Narratives - Febrianto, Aziza Restu; Talenta, Pratama Irwin (Universitas Muhammadiyah Yogyakarta, 2000)
Background: During and after the COVID-19 pandemic, many academics and researchers in English Language Teaching (ELT) have studied a variety of issues faced in various types of online teaching and learning, including examining the efficacy of the Blended Learning (BL) approach as a result of the emergency remote and fully online learning or e-learning in response to the learning-from-home policy. Nevertheless, the researchers discovered that only a few studies employed a narrative inquiry method to explore students' perspectives, stories, and voices relating to their ways of learning during and after the pandemic. Objective: This study helped the researchers better understand the challenges students faced and the adjustments they made, providing unique insights that other methods might miss. Methods: This study addresses that gap by examining the stories and views of nine EFL students from three Indonesian universities who experienced various learning modes during and after the pandemic, including face-to-face, fully online, and blended classes. The students were requested to share their experiences and viewpoints about the BL approach through open-ended questionnaires and semi-structured interviews. The methods and tools from the narrative analysis were then employed to analyze the gathered stories and responses. Findings: The findings indicate that while most students supported BL using appropriate online tools, their understanding of the approach varied, emphasizing the need for specific conditions for its successful implementation. Conclusion: This study contributes to the understanding of the approach variations of BL.